2010
DOI: 10.1016/j.jnutbio.2008.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Yogurt protects against growth retardation in weanling rats fed diets high in phytic acid☆

Abstract: The purpose of this study was to determine the affects of adding yogurt to animal diets which were high in phytic acid (PA) and adequate in zinc (38 μg Zn/g). The PA:Zn molar ratio was 60:1. Zinc status was determined by documenting growth and measuring the zinc concentration in bone (tibia) and plasma. For 25 days, 6 groups (n=6) of Sprague-Dawley weanling rats were fed one of the following AIN-76 diets. Half of the diets contained PA. Four of the diets contained yogurt with either active or heat-treated (ina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…From a safety perspective, a number of repeated-dose studies have been conducted in rodents; no adverse effects were observed in a rat model with orally administered PA in the diet or drinking water at a concentration of approximately 1.0 to 2.5% for up to 12 weeks (17,(57)(58)(59)(60)(61). In addition, exposing the skin to PA may have more advantages than disadvantages.…”
Section: Discussionmentioning
confidence: 99%
“…From a safety perspective, a number of repeated-dose studies have been conducted in rodents; no adverse effects were observed in a rat model with orally administered PA in the diet or drinking water at a concentration of approximately 1.0 to 2.5% for up to 12 weeks (17,(57)(58)(59)(60)(61). In addition, exposing the skin to PA may have more advantages than disadvantages.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that fermentation of feed may reduce the PA:Zn ratio, promoting a better Zn absorption (49) . Other authors, namely Gaetke et al (50) , also have shown that yogurt (both active and heat-treated) protects against growth retardation in weanling rats fed high PA. In animals, feeding PA has been regarded as an anti-nutrient, which reduces P availability, and most research in this field has been aimed at eliminating PA from the animal feed by adding exogenous phytase to it.…”
Section: Possible Mechanism Involved In the Interaction Between Wheatmentioning
confidence: 90%
“…Yogurt was prepared by following the method of Kaur et al(2017) with the addition of 0%, 1%, 2%, 3% and 4% lentil (parched) flour to make treatments; LY0 LY1, LY2, LY3 and LY4 respectively.…”
Section: Lentil-yogurt Preparationmentioning
confidence: 99%
“…However, there are plenty of different problems associated with the sensory and physical properties which hinder the consumer's preference for yogurt. To enhance these physical and sensory attributes the yogurt is incorporated with different stuffs like fruits, pulses, chocolate, grains and nuts (Kucukcetin et al, 2012) (Agil et al, 2013;Zou et al, 2011). Lentil (Lens culinaris) is being acknowledged progressively because of its nutrients profile (Zou et al, 2011) and also keeping the compositional attributes under consideration as it has notable content of carbohydrates, fatty acid fiber and protein (Boye et al, 2010).…”
Section: Introductionmentioning
confidence: 99%